Attrition and Persistence among Visual Arts Students in selected Senior High Schools in Nkwanta South District: Implications for Visual Arts Education in Oti Region, Ghana. - Jejet Godwin (KNUST., 2025)
A thesis submitted to the Department of Educational Innovations in Science and Technology, College of Art and Built Environment, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of MASTER OF PHILOSOPHY IN ART EDUCATION, @ October 2019, Department of Educational Innovations in Science and Technology.